PENGEMBANGAN OUTDOOR SCIENCE WORKSHEET BERBASIS POTENSI LOKAL DESA UNTUK MENINGKATKAN SCIENTIFIC LITERACY - Andi Wibowo (Elementa: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
This study developed outdoor science worksheet based local resources in Palaan village (villages assisted by Raden Rahmat Islamic University). This study aimed to investigate: the appropriateness of outdoor science worksheet and the effectiveness of outdoor science worksheet based local resources in Palaan village to improve student’s scientific literacy. This study employing the development model by Borg & Gall. The research procedure consisted of: preliminary study, planning, developing preliminary product, first revision, preliminary field testing, second revision, main field testing, final product revision, and dissemination. A testing used one-group pretest-postest design. The product testing subjects were students of grade V SDN 2 Palaan. The data were collected through structured interview, questionnaires, and tests. The result of this study was an outdoor science worksheet based local resources in Palaan village. This outdoor science worksheet was appropriate to use in the natural science elementary school learning and could improve student’s scientific literacy effectively. So, village’s local resources could be the one of references to develop teaching materials and also improving student’s scientific literacy.